SELF-IMAGE CONGRUITY: ROLE IN THE FORMATION OF CONSUMER ATTITUDES - Hartini, Sri (Entrepreneur, 2012)
Abstract The more appropriate self-image of consumers with store image, the more positive consumer attitudes toward the retailer, so the higher the commitment and loyalty of consumers. There are four dimensions of self-image congruence of Actual self-image congruence, ideal self-image congruence, Social self-image congruence and ideal social self-image congruence. This study aims to explain the relationships between self image congruence.dengan Consumer attitudes. The study was conducted at a large mall in Surabaya consumers. Purposive sampling with sampling and accidental sampling. The study shows that there are only 2 dimensional image of the actual self and ideal self-image that determine consumer attitudes Keywords: self image, self image store image congruence, attitude. Abstrak Lebih tepat citra diri konsumen dengan citra toko, sikap konsumen yang lebih positif terhadap pengecer, sehingga semakin tinggi komitmen dan loyalitas konsumen. Ada empat dimensi keselarasan citra diri aktual harmoni citra diri, ideal citra diri kesesuaian, citra diri sosial kesesuaian dan ideal citra diri sosial kongruensi . Penelitian ini bertujuan untuk menjelaskan hubungan antara citra diri sikap konsumen congruence.dengan . Penelitian ini dilakukan di sebuah mal besar di Surabaya konsumen. Purposive sampling dengan sampling dan accidental sampling. Studi ini menunjukkan bahwa hanya ada 2 gambar dimensi dari diri yang sebenarnya dan ideal citra diri yang menentukan sikap konsumen. Kata kunci : citra diri, citra toko diri citra keselarasan, sikap .